Perception of 'voicing' among Malaysian ESL learners - Yap, Ngee Thai (Malaysian Association of Modern Languages, 2013)
English has been described as a language with a voicing contrast. However, Avery and Idsardi(2001) in their proposal of a new phonological organization for laryngeal contrasts argued that English has a contrast for aspiration instead of voicing. Using results from a discrimination task involving minimal pairs that contrast in voicing/aspiration in two contexts, word initial and word final contexts, the study presents empirical second language acquisition data from bilingual speakers of English iii Malaysia with Malay, Mandarin, Tamil Li backgrounds to examine the predictions of these two opposing proposals. The results show support for the new phonological model proposed by Avery and Idsardi (2001). The study also show that second language learners are rather successful in acquiring a new system of contrast at the segmental level, but they are less successful when the contrast involves integration of information at the suprasegmental level.